The evolution of Turkish nationalism: From the Ottoman empire to the Republic of Turkiye - Aulia Fatimatuz Zahra; Muhammad Muslim Hidayatulloh (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
The transformation of Turkish nationalism is a unique phenomenon in the ideological transition of a nation. This study aims to explore the shifts in Turkish nationalism from the Ottoman Empire era to the modern Republic of Turkiye. Turkish nationalism will be explored using a qualitative approach, focusing on an in-depth literature review to trace the trajectory of nationalism's transition in Turkish history. Data collection was combined with non-participant observation of the implementation of nationalist practices in daily life or national celebrations in Turkiye. This method was chosen to produce data that provides comprehensive information about Turkish nationalism. Analysis was carried out using Benedict Anderson's 'Official Nationalism' theory to examine the role of state control and Anthony D. Smith's 'Ethnic Core' to understand the process of societal mobilisation. Research results show that the transition of Turkish national identity is very dynamic and undergoes changes in accordance with the needs of Turkish citizens and the policies of their leaders. Turkish nationalism attempts to be shaped by myths and ethnic symbols as well as the collective memory of Turkish citizens regarding their love for the Anatolian homeland, while still implementing top-down governance. During the transition and implementation, Turkish nationalism presents enduring conflicts between the Kemalist/Secular faction and the Conservative faction. The conflict between these two factions manifests as a rejection of Islamic values and of ethnicity, which often coexist. Based on the observations, nationalism is well implemented and arises naturally without coercion within Turkish society